2018
DOI: 10.1007/s00592-017-1097-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sirtuin-1 expression on H3K56 acetylation and oxidative stress: a double-blind randomized controlled trial with resveratrol supplementation

Abstract: AimsSirtuin-1 (SIRT-1) down-regulation in type 2 diabetes mellitus (T2DM) has been associated with epigenetic markers of oxidative stress. We herein aim to evaluate whether an increase in SIRT-1 expression affects histone 3 acetylation at the 56 lysine residue (H3K56ac) in T2DM patients randomly selected to receive either resveratrol (40 mg or 500 mg) or a placebo for 6 months. The primary outcome is changes in the H3K56ac level by variation in SIRT-1 expression and the secondary outcome is the evidence of ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(36 citation statements)
references
References 32 publications
3
28
0
Order By: Relevance
“…It has been observed boosting sirt1 expression through resveratrol treatment led to lower levels of H3K56Ac and also decreased body fat percentage ( Fig. 2) [25]. This study described the inverse relationship between the sirt1 expression with H3K56Ac levels.…”
Section: Sirt1supporting
confidence: 63%
“…It has been observed boosting sirt1 expression through resveratrol treatment led to lower levels of H3K56Ac and also decreased body fat percentage ( Fig. 2) [25]. This study described the inverse relationship between the sirt1 expression with H3K56Ac levels.…”
Section: Sirt1supporting
confidence: 63%
“…Serum level of Sirt1 was measured in this study. Sirt1 was primarily represented as a nuclear protein [ 57 ] and leukocytes (peripheral blood mononuclear cell [PBMC]) have been used for determining Sirt1 expression [ 58 ]. However, it was demonstrated that Sirt1 moves between the nucleus and cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…SIRTs are a family of NAD + dependent histone/protein deacetylases highly conserved through bacteria and eukaryotes [ 111 ]. SIRT1 has been demonstrated to inhibit oxidative stress and inflammation [ 112 , 113 ] and deacetylates a wide range of substrates, including p53, NF-κB, FOXO transcription factors, Ku-70 and PGC-1 α, with roles in cellular processes ranging from energy metabolism to cell survival. Many studies in recent years have highlighted the correlation of SIRT1 activity with AMPK and mTOR pathway [ 114 116 ].…”
Section: Introductionmentioning
confidence: 99%